Construction of Knowledge in Social Work for an emancipating professional praxis in Cuba - Riera-Vázquez, Celia Marta; Fabré-Machado, Idalsis (Prospectiva. Revista de Trabajo Social e Intervención Social, 2023)
The article exposes the research results and the authors' professional practice in their capacity as teachers, trainers, and advisers in Social Work, fundamentally in the central territory of Cuba for more than 10 years. The reflections offered below deal with the need to revalue the role of science (or scientific knowledge) in Social Work (as a discipline and as a profession) in order to develop a truly emancipatory praxis and make viable the academic, political, and professional dialogue in question, as subjects of the (theoretical and practical) transformation of Social Work in Cuba and of the social question. As starting point, it is assumed that the meaning and directionality of the profession is not defined only by discursive content and the will of professional agents and managers, but by its relevance to social dynamics as a specific social practice. Basically, action research is used since the authors are direct participants in the processes that were investigated. Important theoretical and methodological contributions were made that enrich the understanding of the necessary transformation of Social Work in and for Cuba and the process of training its professionals.